The Analysis of Critical Thinking Skills of Primary School Teacher Candidates in Solving Mathematical Problems - Ahmad Arifuddin (UIN Siber Syekh Nurjati Cirebon, 2020)
AbstractThis study is intend to describe the critical thinking skills of primary school Â (MI/SD) teachers candidate and the obstacles they faced in solving mathematical problems. This research is a qualitative research with the research subjects are 36 madrasah ibtidaiyah teacher education students (PGMI), in the fifth semester of IAIN Syekh Nurjati Cirebon. The data collection techniques used are tests and interviews. Meanwhile, the research data were analyzed using descriptive analysis techniques related to critical thinking skills indicators. The results showed that the average of critical thinking ability of primary school teacher candidates in solving mathematical problems especially in geometry material was classified as good, which amounted to 73.57. They are able to formulate problems, determine facts, and use correct evidence in solving mathematical problems. However, most of them have not been able to provide follow-up explanations correctly, thus impacting the difficulty in drawing conclusions. Therefore, a lecturer must be able to build a learning environment that is able to develop their critical thinking to become a qualified teacher.Keywords: critical thinking, mathematics, MI/SD teacher candidate.Â AbstrakPenelitian ini bertujuan untuk mendeskripsikan kemampuan berpikir kritis calon guru sekolah dasar (MI/SD) dan kendala yang dihadapi calon guru MI/SD dalam menyelesaikan masalah matematika. Penelitian ini merupakan penelitian kualitatif deskriptif dengan subyek penelitian yaitu 36 mahasiswa pendidikan guru madrasah ibtidaiyah (PGMI) semester V IAIN Syekh Nurjati Cirebon. Teknik pengumpulan data yang digunakan adalah tes dan wawancara. Sementara itu data hasil penelitian dianalisis menggunakan teknik analisis deskriptif dengan mengacu indikator kemampuan berpikir kritis. Hasil penelitian menunjukkan bahwa rata-rata kemampuan berpikir kritis calon guru MI/SD dalam menyelesaikan masalah matematika materi geometri tergolong baik, yakni sebesar 73.57. Calon guru MI/SD sudah mampu merumuskan masalah, menentukan fakta, dan menggunakan bukti-bukti yang benar dalam menyelesaikan masalah matematika. Namun demikian, sebagian besar calon guru MI/SD belum mampu memberikan penjelasan lanjutan dengan benar, sehingga berdampak pada kesulitan dalam menarik kesimpulan. Oleh karena itu, seorang dosen harus mampu membangun lingkungan belajar yang mampu mengembangkan pemikiran berpikir kritis calon guru MI/SD, agar kemampuan berpikir kritis calon guru MI/SD meningkat dan menjadi guru yang berkualitas.Kata kunci: berpikir kritis, matematika, calon guru MI/SD.